The Influence of Digital Leadership of School Principals and Work Environment on Teacher Performance in Public Elementary Schools in Hulu Palik District, North Bengkulu - Wisdi Risanto; Sudarwan Danim; Muhammad Kristiawan (Yayasan Darusssalam Bengkulu, 2025)
This study aims to analyze the influence of the principal's digital leadership and work environment on teacher performance in Public Elementary Schools in Hulu Palik District, North Bengkulu. The research method used is a quantitative approach with a causal associative design through multiple linear regression analysis, with a sample of 106 teachers selected using proportional simple random sampling techniques. The results showed that the principal's digital leadership had a positive and significant effect on teacher performance (β = 0.220; t = 3.720; sig. = 0.000), as well as the work environment which was proven to have a positive and significant effect (β = 0.394; t = 6.715; sig. = 0.000). Simultaneously, both variables had a significant effect with an F value of 76.479 (p = 0.000) and a coefficient of determination of 59.8%, which means that almost 60% of the variation in teacher performance was explained by these two factors. The novelty of this research lies in the integration of the concept of digital leadership with aspects of the work environment in the context of primary education, which have rarely been studied together before. The contribution of this research is to provide an empirical basis for strengthening school managerial strategies to improve teacher performance through strengthening digital leadership and creating a conducive work environment.